KABA MALIN DEMAN: MENYIASATI DAMPAK DUA FALSAFAH MINANGKABAU DALAM FOLKLOR (Jurnal Gramatika, 2017)
Indonesian folktale is transmitted from one generation to the next by word of mouth. The changes from verbal to written manuscript has in fact undergone a long process. Folktale consists of cultural values of folk/ a particular group of people. Research on folklore is one way to reveal the philosophy contain in the written manuscript. Two of Minangkabau philosophies, extinction philosophy and marriage philosophy, are found in kaba Malin Deman, if imbalance occurs it will create problem in their society. Harmonization is the srategy for the imbalance and also as the function of folklore itself.